Breaking new frontiers: Assessment and re-evaluation of clinical trial design for nutraceuticals - Evans, Malkanthi; Lewis, Erin D.; Antony, Joseph M.; Crowley, David C.; Guthrie, Najla; Blumberg, Jeffrey B. (Frontiers in Nutrition, 2022)
Despite sophisticated study designs and measurement tools, we have yet to create an innovative space for diet and dietary supplements in the health care system. The path is challenging due to current hierarchies of scientific evidence and regulatory affairs. The role of the randomized, double-blind, placebo-controlled clinical trial (RCT) as the only allowed conduit of information for dietary supplementation is problematic. The RCT as a research approach functions well to characterize the benefits and risks of drugs but lacks the sensitivity to capture the efficacy of nutraceuticals. While some facets of RCTs can be relevant and useful when applied to nutraceuticals, other aspects are limiting and potentially misleading when taken in their entirety. A differentiation between guidelines for evidence-based medicine and the evidence required for nutrition spotlight the need to reconceptualize constituents of the RCT and their applicability with relevance to health promotion. This perspective identifies the limitations of the traditional RCT to capture the complexities of nutraceuticals and proposes the N-of-1 as Level 1 evidence better suited for the proof of efficacy of nutraceuticals.